Analisis Produktivitas Alat dan Faktor yang Menghambat Produksi pada Kegiatan Pengupasan Overburden di Tambang Batubara - Maisa Illahi Darni; Hisni Rahmi; Lydia Kartika Basaria Sitompul; Qurratul Ayun; Afni Nelvi; Ericson Ericson (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Overburden removal at Pit B did not meet the production targets for June and July 2025, which were set at 570,698.8 BCM and 400,986.56 BCM, respectively, while the actual production achieved was 507,071.66 BCM and 312,128.23 BCM. This study aims to determine the theoretical productivity of loading and hauling equipment and to identify the factors that hinder the achievement of production targets. The primary data used in this study include the cycle time of loading equipment, the cycle time of hauling equipment, bucket fill factor, and delay time. The secondary data required consist of swell factor, number of passes, bucket capacity, and available working time. The productivity of the loading equipment was 332.58 BCM/hour, while the hauling equipment achieved a productivity of 53.16 BCM/hour, with a match factor of 0.74. This indicates that the loading equipment experienced waiting time during loading operations due to the hauling equipment not operating optimally or at full capacity. The factors inhibiting the achievement of production targets include a narrow, waterlogged, and uneven working face; hard overburden material; a road grade of 16%, which exceeds the standard maximum of 12%; a curve road width of 15 m, which is less than the ideal minimum width of 19.95 m; undulating haul roads; narrow haul road width; and dusty road conditions.